How does line-manager support enhance worker wellbeing? A study in China. Issue 14 (5th August 2020) - Huo, Meng-Long; Boxall, Peter; Cheung, Gordon W.
Abstract: Drawing on the job demands-resources and effort-reward imbalance models, this study investigates the mediating roles of intrinsic motivation and distributive justice in the relationships between line-manager support and employee wellbeing (job satisfaction, work engagement and physical health). Responses to a survey of 357 front-line workers in a Chinese manufacturer were analysed through structural equation modelling. We find, in this context, that line managers are a strong determinant of employee wellbeing when they foster the intrinsic motivation of employees and their perceptions of organisational justice. Such findings are helpful for our understanding of attitudes in the Chinese workforce and underline the value of analysing multiple mediating mechanisms and multiple wellbeing outcomes in human resource management-wellbeing research.